Transforming Organization through Instructional Leadership and Supervision (TOILS) - Tovera Salvador, Jordan; Jade Tovera Salvador, Sunshine (European Scientific Journal, ESJ, 2016)
Instructional leadership and supervision has been subjected in different substantiations in terms of its theoretical standpoints and underpinnings. These are often defined similarly, however, these two have different definitions when it comes to some aspects in the operations within the organization. Instructional leadership involves activities in managing an educational facility, while, supervision is defined as the guidance and oversight of an expert or a more experienced person. In fact, it is usually related with continuous improvement and sustainable development in the classroom instructions. The principal being the head of the school must have a robust platform in leading and managing the educational facility. The main goal of this paper is to establish a concept of instructional leadership and supervision that would answer all the questions in maintaining high competency level of faculty members, sustaining effectiveness of teaching and learning, upholding maximum students’ development programs and transforming the vision, voices, and values of the members of the organization towards solid vision, missions, objectives, and goals.